Lethal P-lacZ insertion lines expressed during pattern respecification in the imaginal discs of Drosophila. - Russell, M.A.; Ostafichuk, L.; Scanga, S. (Genome, 1998)
The imaginal discs of Drosophila are a useful experimental system in which we can study the origin and genetic determination of spatial patterns in development. This involves the separation of the disc-cell population into distinct lineage compartments, based on clonally transmitted expression states of a number of known selector genes. However, these commitments can be abrogated and the compartment boundaries redeployed, when repatterning occurs in cultured disc fragments. This has so far only been explained using the idea of positional information. The genetic basis of this property of the imaginal disc system and its relationship to compartments have not been identified. Here we have screened over 470 recessive lethal P-lacZ enhancer-trap insertions from the Berkeley Drosophila Genome Project for expression after cell death, which initiates pattern respecification in the imaginal discs. The positive lines obtained identify essential genes that may be important for pattern formation. Most show patterned imaginal disc expression, and many have maternal or zygotic effects on embryonic development. One is an allele of schnurri, a gene that encodes a component of the decapentaplegic (dpp) signal transduction pathway used for positional signalling in the embryo and in imaginal discs.